Polymorphisms in genes related to inflammation and endothelial function are associated with ischemic stroke and other vascular events in populations at high risk of stroke - Hong Chen; Hua Luo; Ju Zhou; Ming Yu; Ting Qing; Yanfen Wang; Minjie Shao; Wei Wei; Xingyang Yi (Journal of Central Nervous System Disease)
Background The association of genetic single-nucleotide polymorphisms (SNPs) related to endothelial function, inflammation, and their outcomes remains poorly studied. Objectives To evaluate the occurrence of ischemic stroke (IS) and other vascular events, and relationships between 19 SNPs in genes associated with endothelial function and inflammation with outcomes in a population at high risk of stroke. Design A prospective cohort study and multi-center community-based sectional survey. Methods As a part of the China National Stroke Screening Survey program, the investigation was carried out in southern China from May 2015 to January 2020. Participants from 8 randomly selected. In people who were determined to be at high risk of stroke, 19 SNPs were examined. Over an average follow-up period of 4.7 years, the results of these subjects were monitored using a longitudinal method. A new IS was the primary outcome assessed, and a combination of new vascular events was the secondary outcome. Results In total, 2893 participants were classified as high-risk for stroke, and 2698 were monitored for 4.7 years, resulting in 192 participants (7.1%) experiencing various outcomes. Out of these, 118 individuals (4.4%) had a novel IS, 24 (0.9%) suffered a hemorrhagic stroke (HS), 53 (2.0%) developed myocardial infarction (MI), and 33 (1.2%) passed away. Significant variations have been found in the genotype distributions of TLR4 rs752998, IL6R rs4845625, and TNF rs3093662 among participants with adverse outcomes compared to those without. Generalized multifactor dimensionality reduction (GMDR) analysis identified a substantial SNP-SNP interaction involving HABP2 rs932650, TLR4 rs1927911, and IL6R rs4845625 ( P = .004). The high-risk genotypes of these 3 SNPs were linked to an increased risk of IS (OR = 2.186, 95% CI: 1.247-5.426, P < .001) and total vascular events (OR = 2.367, 95% CI: 1.433-5.798, P < .001), according to multivariate logistic regression adjusted for covariates. Conclusion The incidence of IS and other vascular events was significantly greater among participants who were categorized as being at high risk for stroke. The interacting high-risk genotypes of HABP2 rs932650, TLR4 rs1927911 and IL6R rs4845625 were independently associated with an increased risk of new IS and other vascular events.